PENGARUH PERSEPSI HARGA, KELENGKAPAN BARANG DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN ULANG DI SWALAYAN RAMAI PETERONGAN SEMARANG - Rizky Nur Latifah, 08.3502.0736; Rizal Rifa’i, Alimuddin (Students Journal of Economic and Management, 2012)
This research is to determine how the effect of price perception, Completeness goods and re-location of the purchasing decisions in Ramai supermarket Peterongan Semarang. In this study, population was crowded supermarket buyers on totaling 100 respondents. Sampling technique used is purposive sampling the sample selection subjectively based on certain criteria are a minimum age of 17 years and have never made a purchase at Ramai Peterongan least 1 times. Based on the results of model calculations obtained magnitude determination of Adjusted R2, this means that variation in repeat purchase decision variables able to be explained by the variation of the three independent variables (price, completeness goods, location) while the remaining is influenced by other variables that are not observed . Based on the results of multiple regression analysis can be seen that prices have a positive and significant impact on repeat purchase decisions, (H1 accepted). The effect is statistically significant at probability and produces beta standardized. Probability obtained less Completeness of goods have a positive and significant impact on purchasing decisions (H2 accepted).The effect was statistically significant at the probability and produces beta standardized. Probability earned less Locationof a positive and significant impact on repeat purchase decisions (H3 accepted).The effect was statistically significant at probability and produces beta standardized.beta standardized probability obtained Î± less).Keywords : price perception, completeness goods, atmosphere location, repurchasing decisions